2007
DOI: 10.1161/01.str.0000257981.09329.d2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Role of Transgenic PAF-Acetylhydrolase II in Mouse Models of Focal Cerebral Ischemia

Abstract: Background and Purpose-Platelet-activating factor (PAF) and oxidized unsaturated free fatty acids have been postulated to aggravate neuronal damage in the postischemic brain. Type II PAF-acetylhydrolase (PAF-AH II) not only terminates signals by PAF by its PAF-hydrolyzing activity but also protects cells against oxidative stress. We examined whether PAF-AH II can rescue cerebral neurons against ischemic insults. Methods-Transgenic mice overexpressing human PAF-AH II in neurons were generated and enzyme express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…7A), indicating that PAF-AH (II) protects against CCl 4 -induced hepatic injury mainly in the later phase in contrast to vitamin E. Although the mechanism underlying these processes is not known, the accumulation of oxidized phospholipids in cells may delay the recovery from oxidative stress-induced tissue injury. We have recently reported that transgenic mice expressing PAF-AH (II) under the control of a neuron-specific promoter are highly resistant to reperfusion injury after focal cerebral ischemia, in which oxidative stress is thought to be involved (63). These results, taken together with the present results, indicate that PAF-AH (II) plays a protective role in oxidative stress-induced tissue injury in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…7A), indicating that PAF-AH (II) protects against CCl 4 -induced hepatic injury mainly in the later phase in contrast to vitamin E. Although the mechanism underlying these processes is not known, the accumulation of oxidized phospholipids in cells may delay the recovery from oxidative stress-induced tissue injury. We have recently reported that transgenic mice expressing PAF-AH (II) under the control of a neuron-specific promoter are highly resistant to reperfusion injury after focal cerebral ischemia, in which oxidative stress is thought to be involved (63). These results, taken together with the present results, indicate that PAF-AH (II) plays a protective role in oxidative stress-induced tissue injury in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…This is a critical protective mechanism against exogenous oxidized phospholipids, tert-butyl hydroperoxide oxidative stress, or Ca 2ϩ overloading of neuronal cells because overexpression of PAF acetylhydrolase protects cells from all these apoptotic insults (13,16,34,62,63). This means that for these oxidative insults it is the intact oxidized phospholipid that is responsible for the apoptotic event.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of Transgenic Mice-DNA solution (3 ng/l) was microinjected into the pronuclei of fertilized eggs from BDF1 females as described (21). Identification of transgenic mice was performed by PCR on tail genomic DNA; the sequences of the primers for transgene amplification were 5Ј-CCA GGT TCA CAG TGG AAC AG-3Ј and 5Ј-ATA CAG CAC AGC CAT CCT AC-3Ј.…”
Section: Methodsmentioning
confidence: 99%